Policy Cycle of the Urban Agenda for EU and its Effects on Territorial Cohesion - Neto, Paulo (2019)
This chapter aims to analyse how, in the European Union’s public policy set, policies directed to cities and urban matters have become more relevant. The importance of these policies in the European agenda is seen in Cohesion Policy, but also in the Union’s other policies, with other thematic and sector focuses. The intention is also to analyse to what extent the transversal, trans-sector, multi-scale and transpolicy character – which urban questions have acquired in European policies – are contributing to the development of a new generation of public, national and regional policies, and to achieving higher levels of territorial cohesion. The pertinence of this research is reinforced by the creation of the Urban Agenda for EU, created in 2016 by the European Union, which aims to systematize and reorganize the different Union policies directed to cities and revalue their role in the process of European integration.